Періоди розвитку польської іншомовної освіти (частина 2) - Загоруйко, Людмила (Studies in Comparative Education, 2015)
У статті узагальнено результати другого періоду розвитку польської іншомовної освіти – періоду європейського спрямування (1989 – 2004). Характеризуючи його результати, автором перелічено основні здобутки в галузі іншомовної підготовки студентів, а саме: фактичне поширення навчання іноземних мов, пов'язане з можливістю їх вибору; запровадження обов’язкового вивчення двох іноземних мов; отримання викладачами повноважень для гнучкішої реалізації навчальних програм, а також розроблення авторських програм. Також розглянуто особливості третього періоду розвитку іншомовної освіти у Польщі – періоду європейської інтеграції (2004–2010). Узагальнивши результати третього періоду, автор наголошує на збільшенні кількості годин на вивчення іноземних мов; удосконаленні матеріально-технічної бази навчання іноземних мов; запровадженні обов’язкового складання іспиту з першої іноземної мови на рівні незалежного користувача (В 2). В статье обобщены результаты второго периода развития польского иноязычного образования - периода европейского направления (1989 - 2004). Характеризуя его результаты, автором перечислены основные достижения в области иноязычной подготовки студентов, а именно: фактическое распространение обучения иностранным языкам, связанное с возможностью их выбора; введение обязательного изучения двух иностранных языков; получения преподавателями полномочий для гибкой реализации учебных программ, а также разработка авторских программ. Также рассмотрены особенности третьего периода развития иноязычного образования в Польше - периода европейской интеграции (2004-2010). Обобщив результаты третьего периода, автор отмечает увеличении количества часов на изучение иностранных языков; совершенствовании материально-технической базы обучения иностранным языкам; введении обязательной сдачи экзамена с первой иностранного языка на уровне независимого пользователя (В2). The results of the second period of Polish foreign language education – European orientation period (1989 – 2004) has been summarized in the article. Describing the results of the second period, the author lists the following achievements in the field of foreign language training of students, as: the actual distribution of teaching foreign languages due to the possibility of student’s choice; introduction of compulsory learning of two foreign languages; receiving the authority for flexible implementation of curricula and the development of author programs. Also, the peculiarities of the third period of foreign language education in Poland – European integration period (2004 – 2010) has been revealed. Summarizing the results of the third period, the author stresses on the establishing contacts with international organizations; development of the Polish version of the European Language Portfolio; use of multimedia software for learning foreign languages etc. In 2004 – 2007 a system of students’ language proficiency evaluation has been introduced in the units. This evaluation is conducted based on a scale of foreign language proficiency levels approved by the Council of Europe document «Common European Framework of Reference for Languages». Also it is proposed an experimental learning of a foreign language through the Internet and started training for introduction the system of issuing certificates to raise the level of foreign languages knowledge in students. The author notes that the document «Strategy of Higher Education Development in Poland till 2020», adopted under the EU program «Education and Training 2020» proposes the models of effective organization and management of higher education system, models of quality education management. At the present stage the following priorities to the higher education system in Poland had been set: matching the content and structure of training professionals of all branches in higher education, strengthening its physical infrastructure; increasing mobility of students and lecturers and ensuring their active participation in international education programs.